Moringa oleifera L. leaf extract induces cell cycle arrest and mitochondrial apoptosis in Dalton's Lymphoma: An in vitro and in vivo study. (10th February 2023) - Kumar, Sandeep; Verma, Praveen Kumar; Shukla, Alok; Singh, Rishi Kant; Patel, Anand Kumar; Yadav, Lokesh; Kumar, Sanjay; Kumar, Naveen; Kaushalendra,; Acharya, Arbind
Abstract: Ethnopharmacological relevance: The present work is based on a wide spectrum of evidences available from scientific literature which reflects nutritional and medicinal values of natural products such as plants and their extracts. Moringa oleifera is one such popular plant species amidst indigenous tribal communities which is frequently used to treat ailments such as piles, sore throat, eye and ear infections and even poisonous bites of tropical fauna such as insects or snakes. Furthermore decoction of leaf and bark was used to cure fever and cough. Evidences further reveal that Moringa oleifera L. (Family Moringaceae), is widely distributed not only over the Indian sub-continent, but also over Philippines, Central America, Saudi Arabia and the Caribbean Islands and have been traditionally used to treat cancers since ancient times. However, therapeutic effects of Moringa oleifera on Non-Hodgkin Lymphoma (NHL) are yet to be established. Aim of the study: The study aims to investigate the anti-cancer effects of Moringa oleifera leaf extract against murine NHL Non-Hodgkin cells in vitro and in vivo . Material and methods: The pharmacologically active compounds of Moringa oleifera leaf extract were identified by GC-HRMS analysis. Tests of Moringa oleifera leaf extract's cytotoxicity against DL cells were carried out using the MTT assay. Chromatin condensation along with other morphological alterations were visualized through Fluorescence microscopy. Changes in the mitochondrial membrane potential (ΔΨm), the cell cycle, and apoptosis were analysed through flow cytometer. We tried to identify proteins involved in apoptosis and cell cycle through Western blotting using BALB/c mice as a model organism. Results: GC-HRMS study revealed that a methanol based leaf extract of Moringa oleifera (MOML) comprises of a variety of bioactive chemicals. Our results indicate that MOML successfully reduced the proliferation of DL cells by lowering ΔΨm, changing overall cell morphology. DL cells treated with MOML showed arrested cell cycle at the G2/M phase and substantially up-regulated the expression of p53 and p21. Elevated levels of Bax, Cyt-c, and Caspase-3 and lowered expression levels of Bcl-2 protein suggested induction of apoptosis. Mechanistically, the anticancer efficacy of MOML is attributed to MEK/ERK-mediated pathway inactivation in DL cells. It is also interesting to note that MOML-mediated inhibition of DL growth was accompanied by apoptosis induction and improvement in hematological parameters in DL-bearing mice. Conclusion: Our finding suggested that MOML induces apoptosis and abrogates the growth of Dalton's lymphoma both in vitro and in vivo . Graphical abstract: Image 1 Highlights: Moringa oleifera is extensively used as a traditional medicine due to its various pharmacological and immuno-modulatory properties.. Methanolic leaf extract of Moringa oleifera (MOML) induces mitochondrial dependent apoptosis and cell cycle arrest. MOML increases the survivability and improve physiological changes in DL-induced mice.